2020
DOI: 10.1038/s41598-020-66589-3
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Tuning of Zinc Oxide by Direct Fabrication of Chromium (Cr) incorporated photoanodes for Visible-light driven Water Splitting Applications

Abstract: Herein, we report the synthesis of Cr incorporated ZnO sheets arrays microstructures and construction of photoelectrode through a direct aerosol assisted chemical vapour deposition (AAcVD) method. The as-prepared Cr incorporated ZnO microstructures were characterized by transmission electron microscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy, powdered X-ray spectroscopy, X-ray photoelectron spectroscopy and UV-Vis diffused reflectance spectroscopy. The Cr incorporation in ZnO red sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…These properties (thermal conductivity, high electron mobility, high exciton binding energy, wide band gap) allow ZnO to function under infinite range of applications 11 . Researchers have reported the synthesis and deposition of ZnO nanostructures by sol-gel, hydrothermal and chemical vapours deposition methods on textiles and other substrates for photocatalytic, photovoltaic and functional applications [12][13][14][15][16][17][18][19][20] . These approaches are time consuming and most of them involve two step deposition of ZnO.…”
mentioning
confidence: 99%
“…These properties (thermal conductivity, high electron mobility, high exciton binding energy, wide band gap) allow ZnO to function under infinite range of applications 11 . Researchers have reported the synthesis and deposition of ZnO nanostructures by sol-gel, hydrothermal and chemical vapours deposition methods on textiles and other substrates for photocatalytic, photovoltaic and functional applications [12][13][14][15][16][17][18][19][20] . These approaches are time consuming and most of them involve two step deposition of ZnO.…”
mentioning
confidence: 99%
“…ZnO is also important for photoanode fabrication due to its higher electron mobility and electrochemical stability [8]. Poor photocurrent density, low photocurrent-hydrogen transformation efficiency due to a low absorption coefficient [9], greater surface recombination [10,11], and ultraviolet absorption due to a wide band gap (3.3 eV) limit its practical application [12]. Ion doping, quantum dot sensitization [50,51], and composite fabrication have made ZnO visiblerange active [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…22 In addition, Humaira et al described AACVD method to prepare Cr-doped ZnO photoanode for visible light-driven water splitting application. 23 Recently, some studies demonstrated that group (III) elements with higher valence than Zn can be used as cation dopants for ZnO films. Rich et al fabricated ZnO nanostructures using Al-doped ZnO templates under different applied voltage.…”
mentioning
confidence: 99%